Rehabilitasi Medik pada Nyeri Bahu Hemiplegia Pasca Stroke - Joshua Manurung; Christopher Lampah; Joudy Gessal (Universitas Sam Ratulangi, 2023)
Abstract: According to WHO 2019, stroke is the second leading cause of death worldwide and a significant cause of long-term disability. One of the complications that often occurs after a stroke is hemiplegic shoulder pain that affects the patient with decreased functional use of the arm, decreased quality of life, higher rates of depression, prolonged hospitalization, and impaired rehabilitation. This study aimed to discuss about rehabilitation efforts in post stroke patients with hemiplegic shoulder pain. This was a literature review study by searching three databases (Google Scholar, Pubmed, and Clinical Key) to determine medical rehabilitation for hemiplegic shoulder pain. The results obtained 13 literatures that matched the criteria. Hemiplegic shoulder pain in many ways, such as reducing the functional use of the arm, reducing quality of life, increasing levels of depression, prolonged hospitalization, is to the point of interfering with the recovery process, namely rehabilitation. In conclusion, medical rehabilitation for hemiplegic shoulder pain has shown quite successful efforts in treating or restoring the condition of patient with hemiplegic shoulder pain. It is possible to carry out more extensive research regarding the underlying causes, examinations to diagnose hemiplegic shoulder pain, and more effective rehabilitation in the future. Keywords: medical rehabilitation; hemiplegic shoulder pain; post stroke; quality of life Abstrak: Menurut WHO 2019, stroke merupakan penyebab kematian kedua di dunia dan salah satu penyebab yang bermakna bagi disabilitas jangka panjang. Salah satu komplikasi yang sering terjadi setelah kejadian stroke ialah nyeri bahu hemiplegia yang memengaruhi penderita dengan penurunan penggunaan fungsional lengan, penurunan kualitas hidup, tingkat depresi yang lebih tinggi, rawat inap yang berkepanjangan, gangguan rehabilitasi. Penelitian ini bertujuan untuk mengetahui rehabilitasi medik pada nyeri bahu hemiplegia pada pasien pasca stroke menggunakan metode literature review dengan penelusuran pada tiga database (Google Scholar, Pubmed, dan Clinical Key). Hasil penelitian mendapatkan 13 literatur yang sesuai dengan kriteria. Nyeri bahu hemiplegia dalam banyak hal, seperti penurunan penggunaan fungsional lengan, penurunan kualitas hidup, tingkat depresi yang bertambah, rawat inap yang berkepanjangan, sampai mengganggu proses pemulihan membutuhkan rehabilitasi. Simpulan penelitian ini ialah penanganan rehabilitasi medik pada pasien pasca stroke dengan nyeri bahu hemiplegia telah menunjukkan upaya yang cukup berhasil dalam mengobati atau memulihkan kondisi tersebut Tidak menutup kemungkinan dilakukan penelitian yang lebih luas mengenai penyebab yang mendasari, pemeriksaan untuk mendiagnosis keadaan nyeri bahu hemiplegia maupun rehabilitasi yang lebih efektif di masa mendatang. Kata kunci: penanganan rehabilitasi medik; nyeri bahu hemiplegia; pasca stroke; kuallitas hidup